2020
DOI: 10.2147/jmdh.s279571
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence and Associated Factors of Clinical Vitamin A Deficiency Among Pre-School Children 1–5 Years of Age in Rural Kebeles in Farta District, South Gondar Zone, Ethiopia: A Mixed Methods Study</p>

Abstract: Background: Globally, preschool children are the most at-risk population groups for vitamin A deficiency (VAD). The 2009 World Health Organization (WHO) report stated that one-third (190 million) of preschool children worldwide are deficient in vitamin A. Both clinical and subclinical VAD have been a long-standing problem in developing countries. In Ethiopia, VAD was recognized as a public health problem 4-5 decades before. Since then, researches conducted in other parts of the country still showed varied and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
4
11
0
Order By: Relevance
“…Vitamin A deficiency causes squamous metaplasia of the respiratory epithelium, impairment of the airway mucosal barrier, delay of repair, and reduced airway antioxidants 26 . Recent studies have shown that children with vitamin A deficiency are more vulnerable to respiratory tract infection 9 . Vitamin D, on the other hand, plays an essential role in innate immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin A deficiency causes squamous metaplasia of the respiratory epithelium, impairment of the airway mucosal barrier, delay of repair, and reduced airway antioxidants 26 . Recent studies have shown that children with vitamin A deficiency are more vulnerable to respiratory tract infection 9 . Vitamin D, on the other hand, plays an essential role in innate immunity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that children are more vulnerable to respiratory infections due to their insufficient immunity 8 . Deficiencies of vitamin A and 25‐hydroxy vitamin D (25(OH)D), two essential nutrients for maintaining immunity, have been found to make children susceptible to respiratory infections, including MPP 8‐10 . Although decreased levels of immune‐related factors such as vitamin A and 25(OH)D have been found in many patients with respiratory infections, the correlations between these factors and the disease severity have not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin A deficiency (VAD) is a serious public health problem and one of the nutritional challenges faced by children in low-income countries, especially among those from the poorest communities [1]. Pre-school children are the most vulnerable population group to VAD [2], due to the relatively high demand for vitamin A during this period of rapid growth and development [2]. VAD in this age group is aggravated by low micronutrient intake and high incidence of infections [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…And also high prevalence of vitamin A de ciencies among young children in Vietnam (47.3%) (9). In Ethiopia also vitamin A de ciency is a major public health problem because more than one -third (37.7%) of children had de ciency of serum retinol level, and also the prevalence of clinical vitamin A de ciency, Bitot's spot ranges from 0.8-1.46% and night blindness 1.2% (10)(11)(12). Studies in Ethiopia also showed that Consumption of animal source foods among children age 6-23 months were very low (13) and the prevalence of poor consumption of foods rich in vitamin A was high( 62.3%) (14).…”
Section: Introductionmentioning
confidence: 99%